2023
DOI: 10.3390/nu15143152
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health during the Interpregnancy Period and the Association with Pre-Pregnancy Body Mass Index and Body Composition: Data from the INTER-ACT Randomized Controlled Trial

Abstract: Mental health problems and obesity are two common complications during pregnancy and postpartum. The preconception period is considered an appropriate period for prevention. Therefore, insights into interpregnancy mental health and the impact on weight and body composition are of interest to developing effective weight management strategies. The primary aim of this study is to assess the difference in women’s mental health during the interpregnancy period and the association with pre-pregnancy body mass index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…It was shown that the sense of coherence at the beginning of the next pregnancy was independently related to women's BMI and body fat percentage before pregnancy. Body weight and body fat percentage at the beginning of the subsequent pregnancy appear to be significantly related to a person's ability to cope with stressful everyday events [29].…”
Section: Weight Status Before Pregnancy Weight Gain During Pregnancymentioning
confidence: 99%
“…It was shown that the sense of coherence at the beginning of the next pregnancy was independently related to women's BMI and body fat percentage before pregnancy. Body weight and body fat percentage at the beginning of the subsequent pregnancy appear to be significantly related to a person's ability to cope with stressful everyday events [29].…”
Section: Weight Status Before Pregnancy Weight Gain During Pregnancymentioning
confidence: 99%